Sexual offender's experiences of polygraph testing: a thematic study in three probation trusts*. Issue 1 (2nd January 2018) - Spruin, Elizabeth; Wood, Jane L.; Gannon, Theresa A.; Tyler, Nichola
ABSTRACT: Post-conviction polygraph testing of sexual offenders is controversial and the use of the polygraph as a means of supporting supervision of sexual offenders has only recently been explored. This study quantitatively examined qualitatively offender managers' and sexual offenders' views on the mandatory use of the polygraph in a community-based supervision. Fifteen polygraphed offenders and their 10 offender managers (polygraph group), and 10 non-polygraphed offenders and their ten offender managers (comparison group) were asked about their experiences and perceptions of a mandatory polygraph use. Using thematic analysis, the results provided four main themes: (1) truth detection, (2) perceptions of behaviour change, (3) perceptions of polygraph as part of supervision, and (4) national implementation of polygraph testing. Results suggest several benefits to mandatory polygraph testing as a support for supervision, including offenders making more high-risk disclosures, motivating offender honesty, and aiding offenders' compliance with licence conditions.